Phytogeographical survey of Dalbergia l.f. (Leguminosae-papilionoideae) with productive potential for red propolis in the state of Pará - Santos, Raquel Leão; Pereira, Daniel Santiago; Xavier Júnior, Sebastião Ribeiro; Venturieri, Giorgio Cristino (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
The genus Dalbergia L.f. (Leguminosae-papilionoideae), with pan tropical distribution which comprises about 250 species. Dalbergia have been widely exploted for the production of red propolis, which consists of a complex mixture made by the bees from the red and balsamic resinous material found in the meristematic tissue in many plant species of this genus. The objective of this work is to survey the occurrence of the bee exuberant beehive flora that can be used by Africanized bees to produce red bee propolis in the state of Pará. Thus, the research aimed to carry out the survey in several herbaria that had species of Dalbergia L.f. producers of red exudate in the state of Pará, together with their distribution. Therefore, specific literatures on morphology and taxonomy were consulted involving Dalbergia species producers of red exudate located in Pará. The data collection was obtained from the online platform SpeciesLink; from the IAN (Instituto Agronômico do Norte) herbarium collection of EMBRAPA Amazônia Oriental. The distribution map was elaborated using the software QGIS together with collection data from the species. 204 records were found deposited in 21 herbariums, of which 175 belong to the species Dalbergia monetaria and 29 to Dalbergia ecastaphyllum. Analyzing the collection data, it was noticed that the species were collected in 44 municipalities of the state of Pará, in which Belém and Bragança presented more records. From the survey carried out, it was noticed the predominance of Dalbergia monetaria in the records, showing that it is a species that has potential to be explored; In addition, the work still promotes botanical studies and taxonomic revisions involving the target species of the present study.